The Investigation of Antimicrobial Properties of Ag–Alginate Impregnated Polyester/Viscose Nonwoven Fabric - (:unkn) unknown (My University, 2019)
Alginate is a biomaterial that is used in food, textile and medical industry. Alginate is used in textile industry as sizing agent, thickener andfinishing materials.In addition to this, it is used in medical industry due to its biodegradable and biocompatible properties. The aim of thisstudy is to investigate the antimicrobial properties of Ag–alginate impregnated polyester/viscose nonwoven fabric. In this study, Ag–alginatesolutions were prepared. Polyester/viscose nonwoven fabric with different mixing ratio was impregnated with prepared solutions. Finally,The antimicrobial, EDX and SEM analyses were performed.

Aljinat, gıda, tekstil ve tıp endüstrisinde kullanılan bir biyomateryaldir. Aljinat tekstil endüstrisinde haşıl maddesi, kıvam arttırıcı ve terbiye maddesi olarak kullanılmaktadır. Buna ek olarak biyobozunur ve biyouyumlu özellikleri nedeniyle medikal endüstride de kullanılmaktadır. Bu çalışmanın amacı, Ag-aljinat emdirilmiş polyester / viskon nonwoven kumaşın antimikrobiyal özelliklerini incelemektir. Bu çalışmada Ag-aljinat çözeltileri hazırlanmıştır. Farklı karışım oranlarına sahip polyester / viskon dokunmamış kumaşlar hazırlanan çözeltilerle emdirilmiştir. Son olarak, antimikrobiyal, EDX ve SEM analizleri yapılmıştır.
Ag – Aljinat Emdirilmiş Polyester / Viskon Nonwoven Kumaşın Antimikrobiyal Özelliklerinin Araştırılması
Keywords: Kimya, Uygulamalı; Kimya, Tıbbi; Kimya, Organik; Çevre Bilimleri; Matematik; Fizik, Matematik; Mühendislik, Kimya; Mühendislik, Elektrik ve Elektronik; Endüstri Mühendisliği; Mühendislik, Makine; Malzeme Bilimleri, Biyomalzemeler